The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/s13187-016-1118-y
|View full text |Cite
|
Sign up to set email alerts
|

Learning Needs of Gynecologic Cancer Survivors

Abstract: To define the learning needs of patients with gynecological oncology. The study was performed as a descriptive study. A total of 92 patients were participated. Data were collected using Patient Learning Needs Scale (PLNS). The Pearson correlation test, independent sample t test, and analysis of one-way of variance (ANOVA) followed by Tukey's-B post hoc tests were used for statistical analyses by the SPSS 15.0 software package. The mean age of women's was 50.37 ± 12.20 years. The women's diagnoses were cervical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Two recent Turkish studies reported on the needs of women with gynaecological cancer, revealing a high prevalence of symptoms and unmet palliative care needs (Akkuzu et al, 2018; Seven, Sahin, Yilmaz, & Akyuz, 2016). Akkuzu et al (2018) also identified that women required knowledge on pain management, daily living activities and psychological support. Further international quantitative studies have focused on specific gynaecological cancer subgroups or on the needs of caregivers (Beesley et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Two recent Turkish studies reported on the needs of women with gynaecological cancer, revealing a high prevalence of symptoms and unmet palliative care needs (Akkuzu et al, 2018; Seven, Sahin, Yilmaz, & Akyuz, 2016). Akkuzu et al (2018) also identified that women required knowledge on pain management, daily living activities and psychological support. Further international quantitative studies have focused on specific gynaecological cancer subgroups or on the needs of caregivers (Beesley et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Other potential issues affecting recruitment may include the stigma associated with EC diagnosis, the experience of treatment-related side effects and embarrassment regarding their functional capacity. Importantly, ECS also frequently report the need for resources to help them deal with pain [1] and that pain can impact their ability to remain in lifestyle studies [21]. Interestingly, a recent study found ECS who were exercisers had lower levels of co-morbidity and were more likely to report that feeling better physically and emotionally rather than reducing the risk of disease was the important outcome of exercise[13], which may be useful for care providers trying to educate these women in future approaches.…”
Section: Discussionmentioning
confidence: 99%
“…A significant concern given that evidence from a recent systematic review indicates that inactivity is highly correlated with worse QOL, and even more so for obese ECS [2]. Not surprisingly, gynecologic cancer survivors most frequently report learning needs for coping with pain, daily living activities and psychosocial support [1]. Unfortunately, ECS generally do not engage in lifestyle change of their own accord [20, 25].…”
Section: Introductionmentioning
confidence: 99%
“…People with cancer face a range of common concerns such as the symptoms associated with cancer and its treatment effects (Akkuzu et al, 2018;Beaver & Booth, 2007;Papadakos et al, 2012), fear of recurrence and difficulty communicating with others about their cancer (Papadakos et al, 2012). However, women with gynaecological cancer also report a range of more specific treatment-related concerns.…”
mentioning
confidence: 99%